ANALISIS KELAYAKAN FINANSIAL USAHA PETERNAKAN AYAM PETELUR PADA CV.TAUFIK NUR DI KOTA PALU - Muhammad Muhammad; Hadayani Hadayani; Alimuddin Laapo (Agroland: Jurnal Ilmu-ilmu Pertanian, 2017)
Laying hens farming system of CV. Taufik Nur is the largest of the nine laying    hen farm businesses residing in Sigi Regency.  These laying hen farmings have not yet been able to meet the quota of market demand outside the regency such asPalu city due to their incapability to optimally achieve their production target.  Their production actually can be raisedby means of enlarging their chicken coops as well as increasing the chicken populationsuited to local climatic and management condition.  The purpose of this  research was to analyze the financial feasibility of the laying hen farming system of   Taufik Nur CV.and to analyze the impact of decreasing egg production levels caused by   the chicken death and feed price rises.This research was carried out in October                  to December 2016.  Respondents were purposively determined from the CV. internal parties such as operational workers, manager and an administrative worker.  The NPV of the Taufik Nur CV. was larger than 0 (IDR 2,367,567,450);the IRR was 37.12%  greater than the discount rate of 16%; the net B/C value was 7.64 greater than one; and the PBP was 2.61 less than the age of the business i.e. 2 years 8 months. Based on the results of a sensitivity analysis, this business is still feasible to operatealthough the egg production decrease by 15%and the price of feed concentratesin crease by 37%. Keywords :  Financial analysis, Lying hens, and Sensitivity.